2013
DOI: 10.1021/jf3051736
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Storage Temperature and Packaging on the Sensory, Chemical, and Physical Properties of a Cabernet Sauvignon Wine

Abstract: A Californian Cabernet Sauvignon was stored for 6 months at three different constant temperatures to study the combined effects of storage temperature and packaging configuration. Glass bottles with natural cork, synthetic cork, and screw cap closure, as well as two Bag-in-Box treatments, were used in the experiment. A trained sensory panel was able to detect significant changes in aroma, flavor, taste, mouthfeel, and color attributes among the samples, differences that were found also with various chemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 59 publications
5
33
0
3
Order By: Relevance
“…A study to investigate the combined effect of storage temperature (10, 20 and 40°C) and packaging configuration in Cabernet Sauvignon was described by Hopfer et al. (). After 6 months, several volatile compounds varied significantly between samples with increasing storage temperature with the largest observed changes in acetates and alcohols, with some compounds increasing and others decreasing.…”
Section: Effect Of Elevated Temperature On Volatile Compoundsmentioning
confidence: 99%
“…A study to investigate the combined effect of storage temperature (10, 20 and 40°C) and packaging configuration in Cabernet Sauvignon was described by Hopfer et al. (). After 6 months, several volatile compounds varied significantly between samples with increasing storage temperature with the largest observed changes in acetates and alcohols, with some compounds increasing and others decreasing.…”
Section: Effect Of Elevated Temperature On Volatile Compoundsmentioning
confidence: 99%
“…However, there are also some different viewpoints. For example, Hopfer et al thought that the changes in yellowness and hue value, expressed as b ⁄ and h values, greatly differed amongst the wines mainly owing to the difference in the bottleaging temperature rather than the sealing systems (Hopfer et al, 2013).…”
Section: Variation Of Colour Characteristics In Bottled Winesmentioning
confidence: 99%
“…However, it also has been reported that synthetic plugs effectively prevented the generation of 'corked taste' and provided white wine with fruity aromas (Francis, 2003). Besides bottle stoppers, storage temperature also can cause some differences in aroma, mouthfeel, and colour of bottled wines (Hopfer, Buffon, Ebeler, & Heymann, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of wine, a large number of studies have described the modification and/or evolution of oxygen, carbon dioxide, nitrogen, and sulfites inside the packaging [26]; the oxidative stability of the product [27]; the presence of aromatic compounds [15,18,28,29]; and changes in sensory, chemical [30] or physical properties [29,31]. Moreover, overall mechanisms involved after packaging such as chemical reactions (esterification, hydrolysis, and oxidation), aging, and possible transfer through the packaging or the cap that can produce any loss, increase, appearance or disappearance of aromatic compounds are reported.…”
Section: Influence Of Packaging On Beverage Conservation and Drawbackmentioning
confidence: 99%